Use of management reports and performance of sales managers in an insurance company - Oyadomari, José Carlos Tiomatsu; Duque, Bruno; Nisiyama, Edelcio Koitiro; Dultra-de-Lima, Ronaldo Gomes; Mendonça Neto, Octavio Ribeiro de (Revista Contabilidade & Finanças, 2018)
ABSTRACT This article aims to investigate the relationship between perceptions of the enabling dimension and the technical validity of the management reports of an insurance company and the performance of its sales managers, mediated by the use of these reports. Companies invest resources in providing management reports for business managers to take decisions, so understanding what influences the use of these reports and whether this use is associated with performance constitutes a relevant subject for both academia and professional practice. The results may be useful for organizations that are taking decisions to invest in management reports, showing that technical validity is what best influences the use of these reports, at least in the short term, which is also a contribution to the theory. Secondary data were combined with a survey of 231 respondents from an insurance company and analyzed using the structural equation modeling (SEM) technique via partial least squares (PLS). The article contributes to the literature and management accounting practice by demonstrating that, unlike in previous studies, the enabling dimension does not positively influence the use of management reports. On the other hand, the study shows that technical validity, which is a more tangible dimension of the quality of management reports, is positively associated with their use and that this use influences the performance of the sales managers. Keywords: use of management reports, sales performance, sales managers, insurers, enabling. RESUMO O objetivo deste artigo foi investigar os relacionamentos entre as percepções da dimensão facilitadora e a validade técnica dos relatórios gerenciais e desempenho dos gerentes comerciais de uma seguradora, mediados pelo uso desses relatórios. As empresas investem recursos para fornecer relatórios gerenciais para que os gerentes comerciais tomem decisões. Portanto, entender o que influencia o uso desses relatórios e se essa utilização está associada ao desempenho constituem tema relevante tanto para academia quanto para a prática profissional. Os resultados deste artigo podem ser úteis para organizações que estão tomando decisões de investir em relatórios gerenciais, mostrando que a validade técnica é a que melhor influencia o uso desses relatórios, pelo menos no curto prazo, o que também é contribuição para a teoria. Dados secundários foram combinados com um survey com 231 respondentes de uma empresa de seguros e analisados pela técnica de modelagem de equações estruturais (MEE) por meio do partial least square (PLS). O artigo contribui para a literatura e a prática da contabilidade gerencial ao demonstrar que, diferentemente de pesquisas anteriores, a dimensão facilitadora não influencia positivamente o uso de relatórios gerenciais. Em contrapartida, o estudo mostra que a validade técnica, dimensão mais tangível da qualidade dos relatórios gerenciais, está associada positivamente ao uso dos relatórios gerenciais e que esse uso influencia o desempenho dos gerentes comerciais.